2022
DOI: 10.3390/cancers14184374
|View full text |Cite
|
Sign up to set email alerts
|

SPP1 Derived from Macrophages Is Associated with a Worse Clinical Course and Chemo-Resistance in Lung Adenocarcinoma

Abstract: Osteopontin, also called secreted phosphoprotein 1 (SPP1), is a multifunctional secreted phosphorylated glycoprotein. SPP1 is also expressed in tumor cells, and many studies demonstrated that a high level of circulating SPP1 is correlated with a poor prognosis in various cancers. SPP1 is expressed not only by tumor cells but also by stromal cells, such as macrophages. However, there have been no studies distinguishing the SPP1 expression of cancer cells and tumor-associated macrophages (TAMs). Thus, in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 43 publications
5
44
0
2
Order By: Relevance
“…For instance we observed secreted phosphoprotein 1 (=osteopontin) 25-fold induced in LC patients and this macrophage derived cytokine confers drug resistance in human LC 94 . Similar, matrix metalloproteinase 12 was highly induced (13 and 14-fold in female and male LC patients) and promotes angiogenesis 8 95 .…”
Section: Clinical Genomics Of Lc Tumor Samplesmentioning
confidence: 84%
“…For instance we observed secreted phosphoprotein 1 (=osteopontin) 25-fold induced in LC patients and this macrophage derived cytokine confers drug resistance in human LC 94 . Similar, matrix metalloproteinase 12 was highly induced (13 and 14-fold in female and male LC patients) and promotes angiogenesis 8 95 .…”
Section: Clinical Genomics Of Lc Tumor Samplesmentioning
confidence: 84%
“…For example, SPP1 expression in LUAD tissues was signi cantly higher than in normal tissues, positively correlated with TNM stage, lymph node metastasis, and depth of in ltration, and was associated with poorer prognosis by upregulating COL11A1 expression to promote cell migration and invasion (Yi et al, 2022). And in pancreatic adenocarcinoma, SPP1 expression levels were associated with patient prognosis and immune regulation (Chen et al, 2022), and in lung adenocarcinoma, SPP1 was found to be associated with drug resistance (Matsubara et al, 2022). In a recent study, researchers further investigated the level of serum SPP1 autoantibodies in patients with esophageal squamous cell carcinoma (ESCC) and showed that its expression was signi cantly upregulated compared to the normal group, suggesting that anti-SPP1 autoantibodies are a novel biomarker for the detection of ESCC , and SPP1 is important in prostate cancer (PCa), head and neck cancer (HNC), cervical squamous cell carcinoma (SCC) and other cancers (Zhang et al, 2022, Feng et al, 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoprotein 1 (SPP1), also known as osteopontin, is a multifunctional secreted phosphorylated glycoprotein [ 17 , 18 , 19 ]. SPP1 is produced in a variety of organs, such as the kidneys, liver, brain, lungs, and pancreas [ 17 , 18 , 19 ]. SPP1 is also present in body fluids such as serum, bovine milk, and human urine [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…We recently revealed that SPP1 expression on TAMs correlates with poor prognosis and chemoresistance in lung adenocarcinoma [ 17 ]. In this review, we summarize the significance of TAMs in lung cancers and discuss the importance of SPP1 as a new marker for the protumor subpopulation of TAMs in lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%